2006
DOI: 10.1098/rspb.2006.3515
|View full text |Cite
|
Sign up to set email alerts
|

Telonemia, a new protist phylum with affinity to chromist lineages

Abstract: Recent molecular investigations of marine samples taken from different environments, including tropical, temperate and polar areas, as well as deep thermal vents, have revealed an unexpectedly high diversity of protists, some of them forming deep-branching clades within important lineages, such as the alveolates and heterokonts. Using the same approach on coastal samples, we have identified a novel group of protist small subunit (SSU) rDNA sequences that do not correspond to any phylogenetic group previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 49 publications
3
86
1
Order By: Relevance
“…First, the monophyly of the clade (Rhizaria + Stramenopila) is witnessed, and the corresponding posterior probability is 100%. Compared with the corresponding value (71%) in a previous study (Shalchian-Tabrizi et al, 2006), this value is more convincing. And this clade was also supported by the evidence of expressed sequence taqs (ESTs) (Burki et al, 2007).…”
Section: The Phylogeny Of Eukaryota Based On the Length Stable Parts contrasting
confidence: 51%
See 1 more Smart Citation
“…First, the monophyly of the clade (Rhizaria + Stramenopila) is witnessed, and the corresponding posterior probability is 100%. Compared with the corresponding value (71%) in a previous study (Shalchian-Tabrizi et al, 2006), this value is more convincing. And this clade was also supported by the evidence of expressed sequence taqs (ESTs) (Burki et al, 2007).…”
Section: The Phylogeny Of Eukaryota Based On the Length Stable Parts contrasting
confidence: 51%
“…Due to the differences in taxa sampled and ambiguous alignment, the findings of previous phylogenetic studies based on 18S rDNAs vary extensively from each other (Cavalier-Smith and Chao, 1996;Kumar and Rzhetsky, 1996;Van de Peer and De Wachter, 1997;Burki et al, 2002;Kostka et al, 2004;Nikolaev et al, 2004;Polet et al, 2004;Shalchian-Tabrizi et al, 2006;Shalchian-Tabrizi et al, 2007). Additionally because of the effects of sparse taxon sampling and heterogeneity in the sequence data, the results of the studies based on multiple proteins or protein-coding genes are also quite different from each other (Baldauf et al, 2000;Philippe et al, 2004;Harper et al, 2005;Rodríguez-Ezpeleta et al, 2005;Burki and Pawlowski, 2006;Burki et al, 2007;Hackett et al, 2007;Patron et al, 2007;Kim and Graham, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These taxa were hypothesized to share a single, ancient red algal secondary endosymbiosis that gave rise to the chromophyte plastid present in many photosynthetic chromalveolates such as diatoms and haptophytes and lost secondarily in groups like ciliates and the plastid-lacking cryptophyte lineage Goniomonas. Recently several other protist groups such as telonemids (Shalchian-Tabrizi et al, 2006), katablepharids, centrohelids (Okamoto and Inouye, 2005;Okamoto et al, 2009), picobiliphytes , and rappemonads (Kim et al, 2011) have been suggested to share an affiliation with the chromalveolates. Undoubtedly the quickening pace of environmental genomics research will turn up other candidate taxa affiliated with the ever-growing assemblage of chromalveolates that no longer bears any resemblance to the taxonomic scheme that was originally envisaged by Cavalier-Smith (1998).…”
Section: Algae and Plants In The Evolving Tree Of Lifementioning
confidence: 99%
“…Classification is based on Adl and colleagues (2005) and Not and colleagues (2007). All groups correspond to first and second rank according to Adl and colleagues (2005) except *Super-group and **Phylum (Shalchian-Tabrizi et al, 2006). Fig.…”
Section: Supporting Informationmentioning
confidence: 96%